How old is the Babo Balukbuk Site? The Use of Tradeware Ceramics and Radiocarbon Dating in Identifying the Age of Porac, Pampanga, Philippines - Melendres, Rhayan G. (Hukay; Vol 19 (2014))
Central to the process of doing archaeology is the necessity for under-standing the chronological sequencing of archaeological entities and past events and understanding the method that was used in doing so. Without a firm grasp of this sequencing, archaeologists would not be able to deal with issues of behaviour-al process and evolution. For this reason, dating the past has been one of the most crucial methodological problems facing archaeologists. Two sources of dating were used in identifying the age of Babo Balukbuk, Porac, Pampanga, Philippines namely: tradeware ceramics dating and radiocarbon dating. The system that I developed that was published earlier will be employed in identifying and docu-menting the tradeware ceramics found in the site. Also, the radiocarbon dates will be used to validate and cross-check the dates of the ceramics. Then, this paper will discuss the results of these dating techniques and their implications and signifi-cance in understanding better the pre-Spanish people of Pampanga, Philippines.